Effect of Brochure and Audio Recordings of Testicular Cancer Stories on Testicular Self-Examination: Randomized Controlled Study - Ucar, Ayse Kilic; Aykac, Irem; Tastan, Sevinc (Wiley, 2025)
Objectives: The aim of this study was to determine the effects of a training program based on educational brochures and audio recordings of testicular cancer (TC) stories on testicular self-examination (TSE) and health beliefs among university students. Design: The study had a pretest-posttest, control group experimental design. Sample: This study was conducted with 106 students in Turkey. Method: Data were collected using a personal information form, the Health Beliefs Model (HBM) Scale for TC and TSE, and a form for determining TSE and sharing information. Results: There was a statistically significant difference between the posttest scores obtained by the intervention group, who received the training and the control group on the susceptibility, benefits and health motivation, barriers, self-efficacy, and health motivation dimensions of the HBM Scale (p < 0.05). The percentage of TSE in the intervention group increased from 14.8% to 90.7% after receiving training on TC and TSE, which was significantly different from the pretest and posttest scores of the control group. Conclusions: Training using educational brochures and audio recordings of TC stories had a positive effect on TSE and health beliefs. The results suggest that both training methods can be used to increase social awareness of TC.
Keywords: brochure; early diagnosis; information sharing; testicular cancer; testicular self-examination